Radiometric Wireless Sensor Network Monitoring of Partial Discharge Sources in Electrical Substations. (17th September 2015) - Zhang, Yong; Upton, David; Jaber, Adel; Ahmed, Hamd; Saeed, Bahghtar; Mather, Peter; Lazaridis, Pavlos; Mopty, Alexandre; Tachtatzis, Christos; Atkinson, Robert; Judd, Martin; Vieira, Maria de Fatima Queiroz; et al.
Abstract : A wireless sensor network (WSN) with the potential to monitor and locate partial discharge (PD) in high-voltage electricity substations using only received signal strength (RSS) is proposed. The advantages of an RSS-based operating principle over more traditional methods (e.g., time-of-arrival and time-difference-of-arrival) are described. Laboratory measurements of PD that emulate the operation of a PD WSN are presented. The hardware architecture of a prototype PD WSN is described and the particular challenges of an RSS-based location approach in an environment with an unknown, and spatially varying, path-loss index are discussed. It is concluded that an RSS-based PD WSN is a plausible solution for the monitoring of insulation integrity in electricity substations.